Janur and Ecospiritual Awareness: An Islamic-Javanese Ecotheological Interpretation of Heritage City Mitigation - Widodo Aribowo; Siti Muslifah; Sahid Teguh Widodo; Aloysius Indratmo; Kartini Aboo Talib (Tribakti: Jurnal Pemikiran Keislaman, 2026)
This study examines the making of janur-based Javanese ritual objects as a form of Islamic ecological pedagogy and cultural mitigation in a heritage-city context. The article addresses a gap in Islamic environmental studies, where ecological ethics is often discussed normatively through concepts such as tawhid, khalīfah, amānah, and āyāt kauniyyah, while less attention is paid to how these concepts are embodied in local cultural practice. Based on a participatory qualitative study conducted at Sanggar Sarudjuk, Serengan, Surakarta, involving seventeen children and community facilitators, this research combines participant observation, visual documentation, reflective autoethnography, and symbolic hermeneutics. The findings show that the practice of making janur keris, kembar mayang, and cengkir gading reactivates symbolic memory, trains embodied ecological sensitivity, and translates Islamic environmental ethics into a lived Javanese cultural form. Janur is interpreted not merely as ritual material but as a vegetal medium through which children encounter nature, bodily discipline, intergenerational memory, and awareness of divine trust. The study contributes to Islamic studies by proposing Javanese-Islamic ecotheology as a lived ethical framework rather than a purely doctrinal discourse. It also contributes to heritage-city studies by framing cultural mitigation as the revitalization of ecological, spiritual, and symbolic relations through small-scale participatory practice.